An ultra-long new onset refractory status epilepticus: Winning the battle but losing the war? - Niccolò Orlandi; Giada Giovannini; Laura Mirandola; Giulia Monti; Andrea Marudi; Francesco Mosca; Alessandra Lalla; Giuseppe d'Orsi; Matteo Francavilla; Stefano Meletti (Epilepsy & Behavior Reports, 2022)
New onset refractory status epilepticus (NORSE), is a rare and challenging condition occurring in previously healthy people. The etiology often remains undiscovered and is frequently associated with an unfavorable outcome. We report the electroclinical and neuroradiological evolution of an ultra-long case of NORSE of unknown etiology.A 38-year-old woman with a prodrome of fever, vomiting and diarrhea was admitted to our Intensive Care Unit for refractory convulsive status epilepticus (SE). Her past medical history was unremarkable. Extensive examinations were negative for potential viral, autoimmune and metabolic etiologies. Despite multiple therapeutical attempts with antiseizures medications, anesthetics and immunotherapy, seizures persisted. After nearly 6 months of enduring seizures, SE finally ceased and the patient gradually recovered to a minimum state of awareness. She was then able to communicate through one-word utterances and to understand simple tasks. At a three-years follow-up, she developed multifocal drug-resistant epilepsy, subcortical myoclonus and severe spastic quadraparesis, becoming completely dependent for activities of daily living.To our knowledge, this represents one of the longest cases of NORSE with final status resolution at this time. However, ultra-long SE in this case led to severe and disabling neurological sequelae. Future studies focused on disease modifying treatments for refractory SE are needed.